MARRIAGE RITUAL TEXT OF BALINESE TRADITIONAL COMMUNITY: AN ANALYSIS OF FUNCTIONAL SYSTEMIC LINGUISTICS - Sutama, Putu; Sutjaja, I Gusti Made; Meko Mbete, Aron; -, Mahyuni (e-Journal of Linguistics; Vol. 4. Juli 2010 No. 2)
The Marriage Ritual Text of Balinese Traditional Community (Teks Ritual‘Pewiwahan’ Masyarakat Adat Bali, hereon abbreviated to TRPMAB) in this dissertationis analyzed in the perspective of linguistic studies using the functional systemic linguistictheory. TRPMAB is a dialogic text containing a discussion, and is terminologicallytermed as a conversational text. It refers to the use of Balinese language (Bahasa Bali,hereon abbreviated to BB) in a marriage ritual. There are two inseparable systems in it;they are BB system and social system, which are widely termed as cultural system.The method employed in this study is field method, meaning that the researcherwent directly to the field or to the location where TRPMAP took place. The researcherdirectly took part as both the active and passive participant. In this way, the researchcould observe TRPMAB directly.The population of the study includes all TPRB in Bali. Considering that thepopulation is too wide, then samples were taken to represent all the population. Thesamples total 10 which were obtained from the biggest marriage processions in Bali. Outof the 10 samples, 6 units of text were selected as the corpus of the study. The selectionwas made based on particular criteria including quality. It is this corpus which wasanalyzed to support and examine the hypothesis related to the text analyzed.The analysis of TRPMAB includes: the structure of the texts, the mood, thetransitivity, the theme-rheme and the logical relationship between the clause and theideology. The findings are as follows:(1) TRPMAB is a text which has a number of structural dimensions such as (a)cultural structure, (b) macro structure, that is, the structure related to the situationalcontext made up of field, tenor and mode, (c) micro structure, (d) structure of meaning,that is, the structure related to the sequence of meanings between the participants withinthe dialogue, and (e) the texture, that is, the intact successive relationship of meaningsamong parts of the text.(2) TRPMB is a text which has a particular system of mood according to thesystem in Balinese language. The structure of clausal mood is made up of subjectfollowed predicate (S?P), the structure of clausal mood is made up of mood and residue,and the system of modality is made up of modalization. (3) TRPMB is a text which has macro transitivity termed as transitivity, that is,the system of valency existing among the processes and participants. The processes usedare ordered as follows: mental process (1,361), existential process (1.071), verbal process(461), relational process (222), behavior process (105) and material process (225). Addedtogether, there are 3,445 processes.(4) TRPMAB is a text which has complete composition of theme - rheme such as(a) the theme of intra participants, that is, the theme which occupies the first position inthe structure of mood; (b) the topical theme, that is, the theme which occupies the initialposition in the structure of transitivity; and (c) the textual theme, that is, the theme whichoccupies the initial position in the text.(5) TRAPMAB is a text which is constructed by the logic syntactic and semanticrelationships. As far as the logic semantic relationship is concerned, only expandedrelationship of meaning has been found, that is, a type of relationship in which themeaning of the secondary clause extends or develops the meaning of the primary clauseby elaboration, extension and multiplicity.Apart from being bound to the Balinese cultural context, it is also bound toideology. As far as the Balinese culture is concerned, the ideology referred to is the onewhich is adhered to in the Balinese culture, that is, the one which is related to Hinduismand covers values, esthetics and social patterns. The ideological analysis formulates thatthat the ideology of TRPMAB can be identified through field, participants and mode.